Acute sulphasalazine hepatotoxicity. Issue 726 (April 1986) - Jennings, P. E.; Blandford, R. L.; Rosenthal, F. D.
Abstract : We describe a case of severe sulphasalazine hepatotoxicity. The features described are those of an acute hypersensitivity reaction which responded to drug withdrawal alone as steroids were withheld. Supportive treatment only is recommended for this potentially fatal condition.